Analysis of Volatile Compounds in a Value-Added Jerky by Incorporating Ajwain and Thyme Essential Oils - Elaine Anit; Helga Hernández; Jan Banout; Klára Urbanová (Applied Sciences)
Ajwain essential oil and thyme essential oil naturally contain important bioactive compounds. Various researchers have discovered that these compounds contribute biological benefits for living things such as humans and animals. Bioactive compounds found in essential oils, such as terpenes and terpenoids, possess antibacterial and flavouring qualities, making them promising natural preservatives in the food business. This study investigates the effect of essential oil treatment methods on their incorporation into dehydrated beef and its subsequent sensory acceptability. The meat samples underwent hot air blanching and oil treatment with doses of 0.75 mL and 1.5 mL, respectively. Subsequently, the samples were dried at 55 °C for 6 h after each treatment. The identification and quantification of volatile chemicals were performed using headspace solid-phase microextraction and gas chromatography–mass spectrometry. Thymol, γ-terpinene, p-cymene, and β-pinene were the predominant compounds before and after the treatments. The findings revealed that the application of ajwain and thyme essential oil treatments resulted in significant differences in the final concentration of monoterpenes. However, the sensory evaluation indicated that the ajwain and thyme essential oil samples received similar overall ratings. Consequently, ajwain essential oil could be a suitable alternative to thyme in beef jerky.